Revolution mapping with bump mapping support - Ragragui, Anouar; Ouazzani Chahdi, Adnane; Halli, Akram; Satori, Khalid (Graphical models, 2018)
Per-pixel Revolution Mapping is an image-based modeling and rendering technique or IBMR (Image-Based Modeling and Rendering). It consists of creating a virtual 3D objects without polygonal meshes. This technique uses a single RGBA texture that stores the needed data to generate the revolved surface. The main problem with this technique is that the 3D revolved models are rendered without realistic surface wrinkles. In this paper, we presented an improvement to enhance the realism of the 3D revolved models by combining the revolution mapping and the bump mapping. In order to synchronize between real-time depth scaling of the microrelief and the resulting shading, we have added a scaling factor that makes it possible to have a realistic depth animation. This new technique creates very convincing 3D models with realistic looking surface wrinkles and allows rendering at interactive frame rates. [Display omitted]